Rasionalisasi dalam Komentar-Komentar Masyarakat tentang Pernyataan Yasonna Laoly Terkait Pembebasan Napi Korupsi - Frisca Dilla Frisca; Ngusman Abdul Manaf (Ta'ehao: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2023)
The study of critical discourse is always interesting to be studied in more depth. All forms of media coverage and public arguments make critical discourse analysis research grow. The purpose of this study is to find out the forms of rationalization of the comments of supporters and opponents, views / knowledge that are used as the basis of rationalization, and communities that are made objects of rationalists related to proposals from Yasonna Laoly by using Norman Fairclough's critical discourse analysis method. This type of research is a descriptive qualitative research. The data source used was news from Kumparan, Kompascom, BBCIndonesia, CNNIndonesia, TirtoID, Detikcom, and 20 data accounts in the form of accounts from the Indonesian people regarding Yasonna Laoly's statement of wanting to release corrupt prisoners in the midst of the Corona outbreak. The results showed that the people who commented supporting Yasonna Laoly's statement stated that the plan was the right plan. They argue that the government's decision is a wise decision because it can help corrupt prisoners over the age of 60 get a decent life. People who oppose Yasonna Laoly's statement believe that the plan is a form of injustice from the government which only wants to release the prisoners of corruption and not care about other prisoners.